Endophytic Microbiota Associated with the Root Tips and Leaves of Baccharis dracunculifolia - Santana,Raiana S. M. (2016)
ABSTRACT Although endophytic bacteria impact the health, and ultimately the fitness, of their hosts, our understanding of the diversity of endophytic species remains limited. Here we report on the endophytic microbiota inhabiting the roots, healthy leaves and leaves attacked by a gall-inducing insect of Baccharis dracunculifolia, a species of major economic relevance in South America, using 16S rRNA gene new generation sequencing. Rhodoplanes and Nitrospira were well represented in the communities of roots and leaves; known to be important for nitrogen cycling. The difference in bacterial diversity between healthy and galled leaves was not pronounced. The leaves seem to harbor specialized bacteria with high tolerances to abiotic stresses such as wide variation in temperature, low humidity, shallow and nutrient-poor soils and high solar irradiation. These findings suggest taxon-specific ecological niches in the leaves and roots, which may be the result of different physicochemical characteristics between these structures. This study provides a basis for further investigations and adds significant new information to the current knowledge of the endophytic bacterial composition in B. dracunculifolia.